Occurrence of mycobacteria in bovine milk samples from both individual and collective bulk tanks at farms and informal markets in the southeast region of Sao Paulo, Brazil - Franco, Marília Masello Junqueira [UNESP]; Paes, Antonio Carlos [UNESP]; Ribeiro, Márcio Garcia [UNESP]; de Figueiredo Pantoja, José Carlos [UNESP]; Santos, Adolfo Carlos Barreto [UNESP]; Miyata, Marcelo [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Motta, Rodrigo Garcia [UNESP]; Listoni, Fernando José Paganini [UNESP] (Springer Nature, 2013)
Background: Mycobacterium spp. is one of the most important species of zoonotic pathogens that can be transmitted from cattle to humans. The presence of these opportunistic, pathogenic bacteria in bovine milk has emerged as a public-health concern, especially among individuals who consume raw milk and related dairy products. To address this concern, the Brazilian control and eradication program focusing on bovine tuberculosis, was established in 2001. However, bovine tuberculosis continues to afflict approximately 1,3 percent of the cattle in Brazil. In the present study, 300 samples of milk from bovine herds, obtained from both individual and collective bulk tanks and informal points of sale, were cultured on Löwenstein-Jensen and Stonebrink media. Polymerase chain reaction (PCR)-based tests and restriction-enzyme pattern analysis were then performed on the colonies exhibiting phenotypes suggestive of Mycobacterium spp., which were characterized as acid-fast bacilli.Results: Of the 300 bovine milk samples that were processed, 24 were positively identified as Mycobacterium spp.Molecular identification detected 15 unique mycobacterial species: Mycobacterium bovis, M. gordonae, M. fortuitum, M. intracellulare, M. flavescens, M. duvalii, M. haemophilum, M. immunogenum, M. lentiflavum, M. mucogenicum, M. novocastrense, M. parafortuitum, M. smegmatis, M. terrae and M. vaccae. The isolation of bacteria from the various locations occurred in the following proportions: 9 percent of the individual bulk-tank samples, 7 percent of the collective bulk-tank samples and 8 percent of the informal-trade samples. No statistically significant difference was observed between the presence of Mycobacterium spp. in the three types of samples collected, the milk production profiles, the presence of veterinary assistance and the reported concerns about bovine tuberculosis prevention in the herds.Conclusion: The microbiological cultures associated with PCR-based identification tests are possible tools for the investigation of the presence of Mycobacterium spp. in milk samples. Using these methods, we found that the Brazilian population may be regularly exposed to mycobacteria by consuming raw bovine milk and related dairy products. These evidences reinforces the need to optimize quality programs of dairy products, to intensify the sanitary inspection of these products and the necessity of further studies on the presence of Mycobacterium spp. in milk and milk-based products. © 2013 Franco et al.; licensee BioMed Central Ltd.
Keywords: Bovine; Brazil; Bulk tanks; Mycobacterium spp; Public health; Raw milk; Bacteria (microorganisms); Bos; Bovinae; Corynebacterineae; Mycobacterium; Mycobacterium bovis; Mycobacterium duvalii; Mycobacterium flavescens; Mycobacterium fortuitum; Mycobacterium gordonae; Mycobacterium haemophilum; Mycobacterium immunogenum; Mycobacterium intracellulare; Mycobacterium lentiflavum; Mycobacterium mucogenicum; Mycobacterium novocastrense; Mycobacterium parafortuitum; Mycobacterium smegmatis; Mycobacterium terrae; Mycobacterium vaccae